Histopathology after lidocaine/prilocaine cream administration for vulvar biopsy. (2nd May 2021) - Gonzalez, Rafael; Dunn, Andrew; Williams, Logan; Weber, Jeremy; Erkanli, Alaattin; Havrilesky, Laura J.; Selim, Maria Angelica
Abstract: Background: Case series have described disruptive histopathologic changes following lidocaine/prilocaine cream anesthetic for biopsies. Methods: A study of histopathologic changes was performed following a randomized trial comparing topical lidocaine/prilocaine cream to 1% lidocaine injection anesthesia for vulvar biopsy. Histopathology was reviewed by two independent dermatopathologists blinded to the type of anesthetic. Specimens were scored on six histopathologic criteria described in the literature. Individual scores for each histopathologic feature and the total score across features were compared between the two groups using marginal models with generalized estimating equations. Results: Of 37 specimens reviewed, 19 were randomized to lidocaine/prilocaine cream and 18 to 1% lidocaine. Subjects exposed to lidocaine/prilocaine had the following odds of histopathologic changes, relative to lidocaine‐exposed subjects: acantholysis (odds ratio 2.48; 95% confidence intervals [CI] 0.51, 12.06), clefting (2.42; 0.64, 9.14), pallor/necrosis (1.13; 0.28, 4.50), spongiosis (0.71; 0.18, 2.85), and papillary dermal edema (1.17; 0.41, 3.29). Total scores were not significantly different between treatment arms (risk ratio 0.98; 0.71, 1.35). Conclusion: This histopathologic analysis of a randomized trial between lidocaine/prilocaine cream and injected lidocaine as anesthesia for vulvar biopsy shows the absence of significant disruptive histopathologic features secondary to the type of anesthetic. Additional studies in different clinical contexts are warranted.